2018
DOI: 10.1136/bmjopen-2018-022255
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for mental workload: influence of the working environment, cardiovascular health and lifestyle. A cross-sectional study

Abstract: ObjectivesMental workload is a condition which can negatively influence the overall health of workers. In this study, we aimed to investigate the risk factors for the onset of mental workload, including working conditions, cardiovascular comorbidities and lifestyle habits, in a working population.MethodsThis is a cross-sectional study including 408 workers from a risk prevention service of small/medium companies in Murcia (Spain). Workers from the secondary and tertiary sectors or primary/secondary sectors wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The study by Kazemi et al (2017) showed that, by studying the relationship between mental workload and cognitive failure through the chosen factors using NASA-TLX and the CFQ questionnaire for the data collection method and various statistical methods, the age demographic had a significant effect on mental workload. Another study by López-López et al (2018) analyzed mental workload in multiple sectors in Spain through a cross-sectional study. The results showed that age was independently associated with a higher risk of developing a moderate to significant mental workload.…”
Section: Cross Tabulation Between the Respondent Characteristics And ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Kazemi et al (2017) showed that, by studying the relationship between mental workload and cognitive failure through the chosen factors using NASA-TLX and the CFQ questionnaire for the data collection method and various statistical methods, the age demographic had a significant effect on mental workload. Another study by López-López et al (2018) analyzed mental workload in multiple sectors in Spain through a cross-sectional study. The results showed that age was independently associated with a higher risk of developing a moderate to significant mental workload.…”
Section: Cross Tabulation Between the Respondent Characteristics And ...mentioning
confidence: 99%
“…Supported by the previous research, internal factors make a significant contribution to mental workload. For instance, López-López et al (2018) stated that age has a moderate to significant affect on worker workload. Another study conducted by Şeker (2014) showed that many demographic factors such as age, marital status, education level, and gender have a significant effect on worker workload.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, work-related stress is of increasing interest in our daily lives, given its potential consequences on both employee health and business results (employment leave, absenteeism and poor performance) [3]. Labour has evolved from being mainly a physical activity to having an increasing mental load on the individual [4] and thus, it produces physiological, physical and psychological effects in the short and long-terms, such as negative mood and anxiety [5,6]. Factors such as responsibility, information processing, job-related uncertainty and role ambiguity [7], as well as technostress [8], have contributed to the emergence of new risks to workers' mental health.…”
Section: Introductionmentioning
confidence: 99%